Measuring Electronic Health Record Use in Primary Care: A Scoping Review - Huang, Michael Z.; Gibson, Candace J.; Terry, Amanda L. (Applied Clinical Informatics, 2018)
Background Simple measures of electronic health record (EHR) adoption may be inadequate to evaluate EHR use; and positive outcomes associated with EHRs may be better gauged when varying degrees of EHR use are taken into account. In this article, we aim to assess the current state of the literature regarding measuring EHR use.Objective This article conducts a scoping review of the literature to identify and classify measures of primary care EHR use with a focus on the Canadian context.Methods We conducted a scoping review. Multiple citation databases were searched, as well as gray literature from relevant Web sites. Resulting abstracts were screened for inclusion. Included full texts were reviewed by two authors. Data from the articles were extracted; we synthesized the findings. Subsequently, we reviewed these results with seven EHR stakeholders in Canada.Results Thirty-seven articles were included. Eighteen measured EHR function use individually, while 19 incorporated an overall level of use. Eight frameworks for characterizing overall EHR use were identified.Conclusion There is a need to create standardized frameworks for assessing EHR use.
Keywords: electronic health records; computerized medical record; electronic medical records; meaningful use; primary care; scoping review